2002
DOI: 10.1023/a:1013267504584
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Prostaglandins have cytoprotective effects on gastric mucosa via the influence of various mechanisms. The purpose of this study is to examine the effects of prostaglandins on maturation-dependent spontaneous apoptosis in gastric mucosal cells in vitro, which mimics the apoptosis of gastric mucosal cells related with a rapid cell turnover rate in vivo. Both prostaglandin E1 and E2 inhibited spontaneous apoptosis in a dose-dependent manner and increased the viability of gastric mucosal cells in culture. A number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Prostaglandins (PGs), signaling compounds derived from arachidonic acid (C20:4n-6), also act in apoptosis. In their work on cytoprotective effects of PGs in gastric mucosa, Tsutsumi et al (2002) found that PGE 1 and PGE 2 inhibited maturation-related spontaneous apoptosis in a dose-related way. PGs can also be proapoptotic.…”
mentioning
confidence: 99%
“…Prostaglandins (PGs), signaling compounds derived from arachidonic acid (C20:4n-6), also act in apoptosis. In their work on cytoprotective effects of PGs in gastric mucosa, Tsutsumi et al (2002) found that PGE 1 and PGE 2 inhibited maturation-related spontaneous apoptosis in a dose-related way. PGs can also be proapoptotic.…”
mentioning
confidence: 99%
“…[1][2][3][4] PGE2 enhances interleukin 10 (IL-10) synthesis and modulates the intestinal immune response to dietary antigen. 5,6) The breakdown of systemic tolerance to luminal antigen is reportedly involved in the development of indomethacin-induced enteropathy.…”
mentioning
confidence: 99%
“…42 , 43 EPA gives rise to a different family of eicosanoid mediators, including the 3-series prostaglandin and leucotriene B 5 , which are considered to be less inflammatory than AA-derived eicosanoids. 44 , 45 In addition, AA-derived eicosanoids themselves promote cancer cell growth and progression via several biological processes, including carcinogenic activity, 46 inhibition of apoptosis, 47 promotion of angiogenesis, 25 and cancer cell adhesion, 48 whereas EPA exerts other anticarcinogenic effects through a reduction in the production of free radicals and reactive oxygen species, 49 an increment of insulin sensitivity, 50 and an alteration of estrogen metabolism. 19 These findings support the hypothesis that the balance between EPA and AA is important for regulating the production of mediators and subsequent carcinogenesis and cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%